2004
DOI: 10.1074/jbc.m405576200
|View full text |Cite
|
Sign up to set email alerts
|

Cooperation between Mast Cell Carboxypeptidase A and the Chymase Mouse Mast Cell Protease 4 in the Formation and Degradation of Angiotensin II

Abstract: The octapeptide angiotensin II (Ang II) exerts a wide range of effects on the cardiovascular system but has also been implicated in the regulation of cell proliferation, fibrosis, and apoptosis. Ang II is formed by cleavage of Ang I by angiotensin-converting enzyme, but there is also evidence for non-angiotensin-converting enzyme-dependent conversion of Ang I to Ang II. Here we address the role of mast cell proteases in Ang II production by using two different mouse strains lacking mast cell heparin or mouse m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
47
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 18 publications
(25 reference statements)
3
47
0
Order By: Relevance
“…The recently developed protease-specific knock-out mouse strains have become important tools in identifying such potential in vivo substrates, and examples of substrates identified using these knock-out mice are fibronectin, endothelin, and vasointestinal peptide. Previous work also showed that chymase and CPA3 could cooperate in the degradation of potential substrates (4,6,7,34). Our results also suggest that chymase may be required for the initiation of the degradation process.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The recently developed protease-specific knock-out mouse strains have become important tools in identifying such potential in vivo substrates, and examples of substrates identified using these knock-out mice are fibronectin, endothelin, and vasointestinal peptide. Previous work also showed that chymase and CPA3 could cooperate in the degradation of potential substrates (4,6,7,34). Our results also suggest that chymase may be required for the initiation of the degradation process.…”
Section: Discussionsupporting
confidence: 81%
“…The following mouse strains were used for in vivo and in vitro studies: wild type (WT); the serglycin-deficient mouse strain (SG Ϫ/Ϫ ) (32,33); and the mouse mast cell protease 4-deficient mouse strain (Mcpt4 Ϫ/Ϫ ) (6,34,35). The following mouse strains were used for in vitro studies only: the mast cell-deficient W sash mice; the heparin-deficient mouse strain (NDST2 Ϫ/Ϫ ) (14); the two carboxypeptidase A-deficient mouse strains, Cpa3 Ϫ/Ϫ (which also lack MCPT5) and Cpa3 inact (which carry an inactivating mutation of the catalytic site and maintain MCPT5 expression) (36,37); and the mouse mast cell protease 6-deficient mouse strain (Mcpt6 Ϫ/Ϫ ) (10).…”
Section: Methodsmentioning
confidence: 99%
“…In the case of CPA1 His cleavage has been exploited as a method to remove His 6 tags from the C terminus of recombinant proteins (29). CPA3 has been shown to be able to cleave His 9 of [des-Leu 10 ]angiotensin I in a similar manner as that observed in this study for CPA6 (30). The cleavage of the C-terminal His tag is not an intramolecular reaction, based on the finding that co-transfection of catalytically inactive CPA6 together with the active enzyme resulted in cleavage of the His 6 tag from the inactive enzyme.…”
Section: Discussionsupporting
confidence: 64%
“…This was measured by ELISA, adapting the method of Lundequist et al 26 Briefly, VSMCs were distributed onto 24-well plates at a concentration of 0.5ϫ0 6 cells per well and grown to confluence. After being rendered quiescent as described above, they were stimulated with AGEs (50 g/mL) or control BSA (50 g/mL) for 24 hours.…”
Section: Chymase-dependent Ang Ii-generating Activitymentioning
confidence: 99%